Characteristics, operation and production of the shrimp trawler fleet in Rio de Janeiro State (Brazil) - Paiva, Melquíades Pinto; Té, Gualdino Afonso; Menezes, Antônio Alberto da Silveira (Arquivos de Ciências do Mar, 2017)
This paper deals with the characteristics, operation and production of the industrial shrimp-trawler fleet in the State of Rio de Janeiro (Brazil) in 1993 – 1997 years. The fisheries are directed to catches of the pink-shrimp = Farfantepenaeus brasiliensis (Latreille, 1817) + Farfantepenaeus paulensis (Pérez Farfante, 1967). The fleet is composed by steel and wooden boats, with large variation in the majority of their characteristics, very old in age, having little renovation. The fisheries cover 8 – 9 months/year, due to the closed season, with major activities in July – October. The annual time variation in the shrimp-trawler operations is reflected in the pink-shrimp catches, that reach a little more of 3,8 t/year, when the boats made 181 – 210 fishing days/year. There is a decreasing trend in pink-shrimp production along the years, due to the fall in fishery productivity.